CaMKII activity contributes to homeometric autoregulation of the heart: A novel mechanism for the Anrep effect. (14th June 2020) - Reil, Jan‐Christian; Reil, Gert‐Hinrich; Kovács, Árpád; Sequeira, Vasco; Waddingham, Mark T.; Lodi, Maria; Herwig, Melissa; Ghaderi, Shahrooz; Kreusser, Michael M.; Papp, Zoltán; Voigt, Niels; Dobrev, Dobromir; et al.
Abstract : Key points: The Anrep effect represents the alteration of left ventricular (LV) contractility to acutely enhanced afterload in a few seconds, thereby preserving stroke volume (SV) at constant preload. As a result of the missing preload stretch in our model, the Anrep effect differs from the slow force response and has a different mechanism. The Anrep effect demonstrated two different phases. First, the sudden increased afterload was momentary equilibrated by the enhanced LV contractility as a result of higher power strokes of strongly‐bound myosin cross‐bridges. Second, the slightly delayed recovery of SV is perhaps dependent on Ca 2+ /calmodulin‐dependent protein kinase II activation caused by oxidation and myofilament phosphorylation (cardiac myosin‐binding protein‐C, myosin light chain 2), maximizing the recruitment of available strongly‐bound myosin cross‐bridges. Short‐lived oxidative stress might present a new facet of subcellular signalling with respect to cardiovascular regulation. Relevance for human physiology was demonstrated by echocardiography disclosing the Anrep effect in humans during handgrip exercise. Abstract: The present study investigated whether oxidative stress and Ca 2+ /calmodulin‐dependent protein kinase II (CaMKII) activity are involved in triggering the Anrep effect. LV pressure–volume (PV) analyses of isolated, preload controlled working hearts were performed at two afterload levels (60 and 100 mmHg) in C57BL/6N wild‐type (WT) and CaMKII‐double knockout mice (DKO CaMKII ). In snap‐frozen WT hearts, force–pCa relationship, H2 O2 generation, CaMKII oxidation and phosphorylation of myofilament and Ca 2+ handling proteins were assessed. Acutely raised afterload showed significantly increased wall stress, H2 O2 generation and LV contractility in the PV diagram with an initial decrease and recovery of stroke volume, whereas end‐diastolic pressure and volume, as well as heart rate, remained constant. Afterload induced increase in LV contractility was blunted in DKO CaMKII ‐hearts. Force development of single WT cardiomyocytes was greater with elevated afterload at submaximal Ca 2+ concentration and associated with increases in CaMKII oxidation and phosphorylation of cardiac‐myosin binding protein‐C, myosin light chain and Ca 2+ handling proteins. CaMKII activity is involved in the regulation of the Anrep effect and associates with stimulation of oxidative stress, presumably starting a cascade of CaMKII oxidation with downstream phosphorylation of myofilament and Ca 2+ handling proteins. These mechanisms improve LV inotropy and preserve stroke volume within few seconds. Key points: The Anrep effect represents the alteration of left ventricular (LV) contractility to acutely enhanced afterload in a few seconds, thereby preserving stroke volume (SV) at constant preload. As a result of the missing preload stretch in our model, the Anrep effect differs from the slow force response and has a different mechanism. The Anrep effect demonstrated two different phases. First, the sudden increased afterload was momentary equilibrated by the enhanced LV contractility as a result of higher power strokes of strongly‐bound myosin cross‐bridges. Second, the slightly delayed recovery of SV is perhaps dependent on Ca 2+ /calmodulin‐dependent protein kinase II activation caused by oxidation and myofilament phosphorylation (cardiac myosin‐binding protein‐C, myosin light chain 2), maximizing the recruitment of available strongly‐bound myosin cross‐bridges. Short‐lived oxidative stress might present a new facet of subcellular signalling with respect to cardiovascular regulation. Relevance for human physiology was demonstrated by echocardiography disclosing the Anrep effect in humans during handgrip exercise.